SIMBOL DAKWAH DALAM SENI PERTUNJUKAN KETOPRAK SARIDIN DI BLORA - Afifudin Az Zubaidi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2025)
Traditional performing arts have a strategic role in conveying religious messages culturally within society. One of these art forms is ketoprak, which continues to survive and develop among Javanese communities. This study aims to analyze da’wah symbols in the Ketoprak Saridin performance by the Asmara Sri Budaya group in Blora and to interpret their meanings in representing Islamic teachings. This research employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. Data analysis was conducted using Charles Sanders Peirce’s semiotic theory to interpret da’wah symbols found in dialogues, storylines, characters, and dramatic actions. The results indicate that the Ketoprak Saridin performance contains da’wah symbols representing values of monotheism, simplicity, honesty, patience, trust in God, and criticism of arrogance and greed. These symbols are conveyed contextually through local language and dramatic narratives, making the messages easily understood by the audience. This study confirms that Ketoprak Saridin functions not merely as entertainment but also as an effective medium of cultural da’wah communication within rural communities.